Translation of the Mayo Elbow Performance Score (MEPS) into German (MEPS-G) - Schneider, Marco M.; Nietschke, Rainer; Burkhart, Klaus J.; Hollinger, Boris; Marquardt, Jonas; Schöttker-Königer, Thomas; Morrison, Fiona; Zimmerer, Alexander; Papen, Anna (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background The Mayo Elbow Performance Score is a clinical assessment to rate the performance of the elbow from a medical and/or therapeutic perspective. It is simple and efficient to operate and therefore frequently used in research as well as in clinics. However, an adequate translation of the MEPS into the German language and a verification of the quality criteria for the use in the German health system are currently lacking.Goal of the Study The aim of this study is to translate the MEPS and to review the applicability of the German version (MEPS-G) in Germany.Materials and Methods The translation was undertaken on the basis of a guideline for cultural adaptation. Two independent translations were created, combined and translated back into English by two native speakers. The back translations were reviewed and the German version was amended accordingly. The suitability of the final questionnaire was verified in a pretest with 73 participants.Results The MEPS was converted into the German version MEPS-G and was tested. Apart from minor adjustments, the questionnaire was translated into German without difficulty. The time to complete the assessment was on average 2.5 min (± 1.6).Conclusion First analyses of the psychometric properties of the German MEPS showed identical values as the English version. The detailed quality criteria will be reviewed in a subsequent study.Hintergrund Der Mayo Elbow Performance Score (MEPS) ist ein klinisches Assessment, um die Leistungsfähigkeit des Ellenbogens aus therapeutischer Sicht zu bewerten. Aufgrund seiner einfachen und kurzen Durchführbarkeit findet er in der Forschung und Praxis häufig Anwendung. Eine adäquate Übersetzung des MEPS ins Deutsche sowie eine Prüfung der Gütekriterien für eine Anwendung im deutschen Gesundheitssystem haben allerdings noch nicht stattgefunden.Ziel der Arbeit Ziel dieser Studie ist es, den MEPS zu übersetzen und die deutsche Version (MEPS-G) auf seine Anwendbarkeit in Deutschland zu überprüfen.Material und Methoden Die Übersetzung erfolgte anhand einer Leitlinie zur kulturellen Adaption. Es wurden 2 unabhängige Übersetzungen erstellt, diese zusammengeführt und anschließend von 2 Muttersprachlern ins Englische rückübersetzt. Die Rückübersetzungen wurden überprüft und die deutsche Version erneut angepasst. Die endgültige Übersetzung des Fragebogens wurde in einem Pretest mit 73 Probanden auf seine Anwendbarkeit und Eignung überprüft.Ergebnisse Bis auf kleine Anpassungen konnte der Fragebogen problemlos ins Deutsche übersetzt werden. Die Ausfülldauer betrug durchschnittlich 2,5 min (± 1,6).Schlussfolgerung Die Übersetzung und vorläufige Analysen der psychometrischen Eigenschaften der deutschen Version des MEPS zeigen vergleichbare Werte wie die des englischen Originals. Weitere Studien zu Aspekten der Reliabilität und Validität und genauen Analyse der psychometrischen Eigenschaften des MEPS sind in Arbeit.
Keywords: MEPI; Mayo Elbow Performance Index; elbow; version; transformation